(untitled) (Experimental biology, 2025)
The study focuses on habitat use and behavioral characteristics of the Eurasian eagle-owl (Bubo bubo) at Shakpak Pass situated in the Western Tien Shan. The study aims to elucidate the species’ ecological adaptations and conservation requirements, marking the inaugural use of GPS/GSM telemetry to track spatial movements. The tracking data offers detailed insights into the owl’s ecology, including its movement patterns, hunting behavior, and habitat use. The study emphasizes the species’ adaptability to various environments and contributes to understanding Bubo Bubo’s survival strategies and habitat requirements. The findings hold practical significance for avian ecology and conservation science.